Evaluasi Yuridis terhadap Penerapan Surat Keputusan Perumahan dan Permukiman Kumuh di Provinsi Bali Berdasarkan Permen PUPR No. 14/PRT/M/2018 - Graha, I Made Satya; Pradayani, Santi; Gayatri, Trisna (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This research aims to evaluate the Decree on Slum Settlements in Bali Province based on Permen PUPR No. 14/PRT/M/2018 Research methods: This research uses a normative juridical approach. There are five housing and slum settlement decrees in Bali Province which were used as sampling for evaluation in accordance with the research objectives. Findings: This research found discrepancies with the lex superior Permen PUPR No. 14/PRT/M/2018. Not accordance with the legal principle of lex superior derogat legi inferiori. Implication: From the five regemcies/cities, only three cities complied in full with Permen PUPR No. 14/PRT/M/2018. In the future, the formation of SK must comply with the above regulations.